Efeito de doses de nitrogênio em cobertura na cultura do milho em consórcio com o capim-paiaguás e feijão guandu - Bessa, Stephanie Vicente de (2017)
In Brazil it is recommended the bovinoculture to pasture, and food may be offered to cattle throughout the year. The degradation of pastures has been one of the problems encountered by livestock, due to the fact that it directly affects the productive chain of the animals in their initial phase of fattening. The objective of this study was to evaluate the effect of nitrogen levels in topdressing on the corn crop in consortium with paiaguás grass and pigeon pea. The experimental dsign was factorial experiment 2x4, being two systems of corn consortium + paiaguás grass (M + C) and corn + paiaguás grass + pigeon pea (M + C + G) systems, with four nitrogen doses (0,80, 160 and 240 Kg ha- 1). The plots contained a total area of 17.5 m2 constituted with six lines of five-meter long corns. The four central lines were considered useful, with a half meter being removed from each end. The corn crop was mechanically sown by means of a seeder- fertilizer, with spacing of 0.70 m and 5 seeds per meter. The forage seeds were mixed with the fertilizer and stored in the fertilizer compartment of the seeder and deposited at a depth of 0.08 m, below the corn seed, in the amount of 5.2 kg ha-1, with a cultural value of 46%. The pigeon pea was planted manually in the corn line, placing 10 seeds per meter. In the reproductive stage of hard corn grain, the plants were harvested for the production of silage with 83 days after germination. After the evaluations, the corn, grass and pigeon pea plants were manually cut, at a height of approximately 0.45 m, in the central lines with 2m length per plot (3 m2), using part of the useful plot. Part of the crushed mass was packed in mini silos of PVC pipes. After 31 days the mini silos were opened where central samples were removed, discarding the lateral ones, which were sent to the laboratory for the performance of the bromatological analysis. At the time of corn harvest, the dry mass of the aerial part of the paiaguás grass was determined, determinations in the pigeon pea were carried out in two other periods in the inter-harvest period, at 72 and 245 days after corn harvest. The results were evaluated by analysis of variance using the Sisvar 4.2 program. For the consortiums it was used the test of comparison of means and for the doses of N to regression. Considering the treatments, the dose that best fits the consortium system corn consortium + paiaguás grass is 160 kg ha-1 N and for the consortium corn + paiaguás grass + pigeon pea the most appropriate dose is 120,5 kg ha-1 N.